2011
DOI: 10.1007/s11250-011-9819-z
|View full text |Cite
|
Sign up to set email alerts
|

Rumen development and growth of Balouchi lambs offered alfalfa hay pre- and post-weaning

Abstract: The consumption of solid feed is essential for successful transition from a pre-ruminant to a functional digestive tract. Lambs fed starter rations containing highly fermentable carbohydrates often experience dramatic changes in concentrations of rumen and blood metabolites. The optimal amount of roughage required in the diet of pre-ruminant animals is still unclear. The objective of this study was to determine the effect of feeding alfalfa hay on performance and rumen development in young Balouchi lambs. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
6
28
0
2
Order By: Relevance
“…In their study of growing lambs, Norouzian et al (2011), however, found no effect of inclusion of 30% PBP on DMI. Studies of early lactation dairy cows have shown no effect on DMI when 15% PBP (ensiled or dried) was included in the diet (Bohluli et al 2009;Rezaeenia et al 2012).…”
Section: Discussionmentioning
confidence: 88%
“…In their study of growing lambs, Norouzian et al (2011), however, found no effect of inclusion of 30% PBP on DMI. Studies of early lactation dairy cows have shown no effect on DMI when 15% PBP (ensiled or dried) was included in the diet (Bohluli et al 2009;Rezaeenia et al 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the carcass yield showed a decrease in lambs born in the autumn. The differences between the groups in terms of heart, liver, reticulo-rumen and small intestine which are defined as supply organs may be explained by the fact that lambs born in the autumn received the solid feed earlier than those born in the winter due to pasture access (Norouzian et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While PBP is high in crude protein (158.2 g/kg) and ether extract (EE) (69.5 g/kg) and hence a valuable feed for ruminants (Behgar et al, 2009), its nutritive value is subject to variation due to de-hulling process, pistachio cultivar and growing conditions (Bagheripour et al, 2008). Pistachio by-products (sun-dried or as silage) have recently come to be used in diets for dairy cows (15% DM, PBP) (Mokhtarpour et al, 2012), growing calves (18% DM, PBP) (Shakeri et al, 2012) and sheep (30% DM, PBP) (Norouzian et al, 2011). Phenolic compounds and tannins have been defined as secondary metabolites of PBP (Bohluli et al, 2009;Ghasemi et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%